Relief the tax card games / Nurul Fatihah Ali ... [et al.] - Ali, Nurul Fatihah; Shamsudin, Nurul Izzah; Majdan, Nursyazwani; Rosli, Norshahida; Ariffin, Nurul Azrin (Universiti Teknologi MARA, Kedah, 2023)
The product that our group has invented is a teaching tool on tax exemption that emphasizes Malaysia's perspective. Our team created a card game called "Relief the Tax" for our teaching tool, which will be a deck of playing cards. The OECD defines tax as an obligatory, unrequited payment to the national government. Tax is the amount the government requires people to pay according to income and property. The taxes gained by the government will be used to assist the cost of government in services, goods and activities that the government has been handling. Tax is vital due to its contribution to a country’s economic development. Despite the importance of tax, some people do not take it seriously and have slight knowledge about tax exemption. The objectives of this innovative card game are to educate individuals about tax exemptions as well as to raise awareness among individuals that will lead to more people taking advantage of tax exemptions. In this game, we have selected ten Gs under Relief in Lembaga Hasil Dalam Negeri Malaysia (LHDN) explanatory notes. Each of these Gs has a group of four cards containing information based on LHDN explanatory notes. To play the game, three players are needed where each player receives an equal number of cards. The cards have to be shuffled first before dealing the cards equally to the players. Then, the dealer begins by requesting a card from each player to complete the G’s information. Once the first player gives his card, another player will continue asking for cards until a mistake is made, then another player will take turn to request for other cards. The four cards must be placed face down on the table in front of the player who has a complete G. The player with the most sets is the winner. The card games we invented have commercialization potential and can later be bought by those who are interested in learning about the tax exemption in an entertaining way.